Proposed new scheme interior design for Nescafe Coffee House at 1 & 3 Jalan Telawi 3 Bangsar Baru 59100 Kuala Lumpur / Afizul Adnan - Adnan, Afizul (Faculty of Architecture, Planning and Surveying, 2007)
The proposed of this final project is to realize the design process that involve in the preliminary findings, analysis case study by synthesizing Diploma of Interior Architecture. From the research that I have done, every design processes for cafe must be highlight on certain aspect such as the project objective, accommodation of site proposal and concept that relate to the design project. The suggested title of this project is Proposed New Scheme Interior Design for Nescafe Coffee House at 1 & 3 Jalan Telawi 3, Bangsar Baru, 59100 Kuala Lumpur. Before writing this documentation, a lot of procedures has to be met and must follow a systematic process. Various important factors in site analysis must be considered especially inside the existing space including the surrounding of the building. The first step before I started this project is to identify constraints and limitations of the existing site, interior spaces and the exterior activities. This is extremely important because it aimed to explain the site problem is and to finalize the solving ideas for the project. Beside that, the research of interior space must also be considered as a case study. The nature of the case study directly or indirectly related to the project that I have proposed. This will help me to make a systematic planning before I started to propose a new design about this coffee house. Several important aspects must be considered to ensure the space function. Such as the traffic flow, space requirement, the anthropometric and ergonomic of space always are to fulfill user’s needs and comfort. The design made should fulfill the character of users demand and also match the concepts that need to be shown. Therefore a good study case and research must be strong enough to support the problem solving. In this case I do go to many places and interviewing individuals that professional in it profession of restaurant and cafe to collect as many data and information to cover up my case study before I am started to plan any design process. By creating this Nescafe Coffee House, it is hoped that it will be able to give benefits to the visitors and customers, society and through out the country.